Auditory and Contextual Contributions to Memory Lability and Synaptic Destabilization in the Amygdala - (:unkn) unknown (My University, 2018)
Pavlovian fear conditioning provides a way to investigate memory formation and retrieval. During fear conditioning, a conditional stimulus (CS) is paired with an aversive outcome and the CS acquires aversive value over several pairings. The CS may then be presented during a retrieval session where fear responding is measured as an indicator of memory strength. Retrieval sessions may allow for the incorporation of new information into the original memory trace by destabilizing amygdala synapses. However, the specific circuits and neural inputs that contribute to memory lability and synaptic destabilization during a retrieval session are poorly understood. Previous work has shown that contextual novelty during an auditory retrieval session is necessary for memory lability, suggesting that brain regions encoding auditory and contextual information interact during memory retrieval. The dorsal hippocampus and auditory thalamus play selective roles in processing contextual and auditory information, respectively, during fear conditioning. In the current study, we manipulate functional inputs from each region to determine how each impacts memory lability at amygdala synapses. We found that 1) silencing auditory thalamic inputs in the amygdala during a brief retrieval session reduces fear to an auditory cue and leads to long lasting reductions in fear, and 2) inactivation of the dorsal hippocampus prior to training allows for memory impairment when anisomycin is infused into the amygdala after a retrieval session in an anisomycin resistant memory. This work highlights an important role for brain regions processing sensory information during training and the impact on fear memory recall and modification.
Keywords: AMPA receptor; Amygdala; Destabilization; Hippocampus; Reconsolidation; Thalamus